SMALL INDUSTRY CONTRIBUTION TO IMPROVING COMMUNITY WELFARE: KONTRIBUSI INDUSTRI KECIL DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT - riski aseandi (Jurnal Riset Ilmu Ekonomi, 2022)
This study aims to determine the efforts to maintain small industrial businesses carried out by purun hat craftsmen in Suka Makmur Village, Binjai District, Langkat Regency. The method used is qualitative with key informants from the Village Head and Purun Hat Craftsmen through interview instruments. Based on the results of the research conducted, it can be concluded that the contribution of the purun hat small industry to increasing the welfare of purun hat craftsmen in Suka Makmur Village, Binjai District, Langkat Regency is very realistic and real because the efforts made by the craftsmen are able to meet family needs for primary, secondary, nor tertiary. Then seen from the aspect of income and business efficiency, it turns out that the industry has profits and is efficient to maintain and continue because it has an efficiency value of greater than one.